Development of KARGU Fun Games Card Media for Unggah-ungguh Basa Jawa Learning - Soikhotul Maghfiroh; Joko Sukoyo; Nur Hanifah Insani (RETORIKA: Jurnal Ilmu Bahasa, 2026)
Field observations show that students often experience boredom and difficulties in unggah-ungguh basa Jawa learning, so a solution is needed to overcome this problem. This study was conducted to develop interactive card-based learning media to support the unggah-ungguh basa Jawa learning. The research design used was Research & Development (R&D) through the ADDIE development model with the stages of Analysis, Design, Development, Implementation and Evaluation. Data collection techniques used questionnaires and observation, which were then analyzed descriptively through the stages of data reduction, data presentation, and verification. The result of this research is the creation of a card-based learning media called Unggah-ungguh Card (KARGU) Fun Games. This learning media consists of two levels of games that can support students' language skills. Level one is a vocabulary guessing game used to help the students proficiency in Javanese vocabulary, while level two consists of dialogue exercises to familiarize students with speaking Javanese properly and correctly. The development was adapted to the Unggah-ungguh basa Jawa outcomes of phase F to support students' speaking competence. Based on the validation test results, it was concluded that this media is suitable for use in learning.